India : Asset Prices and the Macroeconomy - Purfield, Catriona (Washington, D.C. : International Monetary Fund, 2007)
This paper examines rising asset prices in India. For the most part, asset prices in India reflect structural factors but the risk of a correction cannot be ruled out. However, at this juncture monetary policy may not be the most effective tool to safeguard financial stability because (i) India's economy is undergoing rapid structural change making it difficult to identify price misalignments; (ii) the macroeconomic impact of an asset price correction is likely to be small; and (iii) the relationship between monetary policy and asset prices is also weak. Targeted changes in financial regulations are better tools to address potential risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet